Auditors' perceptions of environmental issues and its implications for the consideration of environmental matters - Chiang, CKH (Manukau Institute of Technology, 2006)
This study investigates New Zealand auditors’ perceptions on environmental issue and considers their possible implications for the consideration of environmental matters in financial audits. Information used in this study was gathered from a postal survey questionnaire. Survey responses indicated that auditors seem unable to translate their personal views on environmental issues to the auditing sphere of activity and they seem generally ill-informed about environmental matters. There appears to be a conflict between auditors’ awareness of environmental issues and their ability to translate this into their audit practice in considering environmental matter sin financial reports.
Keywords: Auditors; Environmental matters; Financial audits; Survey